2022
DOI: 10.3390/ma15103604
|View full text |Cite
|
Sign up to set email alerts
|

Surface Topographic Features after Milling of Additively Manufactured AlSi10Mg Aluminum Alloy

Abstract: The article presents selected issues related to material quality manufactured by selective laser sintering of AlSi10Mg alloy powder after milling. The workpiece was prepared and machined by down-milling and up-milling with tools made of high-speed steel. Breaches, pores and failure-like cracks on the machined surface were found, which negatively influenced the values of 3D surface roughness parameters. The occurring phenomena were analyzed and proposals for their explanation were made. The results of this rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…When milling surfaces after metallic 3D (three-dimensional) printing, material cracks may remain on the surface after processing. In [ 18 ], the test results showed the presence of cracks and breaches on the milled surface. It was shown that the depth and size of the cracks depend on the cutting edge feed and the milling method.…”
Section: Introductionmentioning
confidence: 99%
“…When milling surfaces after metallic 3D (three-dimensional) printing, material cracks may remain on the surface after processing. In [ 18 ], the test results showed the presence of cracks and breaches on the milled surface. It was shown that the depth and size of the cracks depend on the cutting edge feed and the milling method.…”
Section: Introductionmentioning
confidence: 99%
“…For example, measurements of the parameters of the geometrical structure of the surface in terms of surface defects and surface roughness require an individual approach, which must consider the type of material and the conditions for the measurement. For example, measurements of the parameters of materials produced by selective laser sintering required the selection of the kind of lighting and a specialized optical path for the imaging method [7]. The choice of the type of illuminator is a crucial task from the point of view of industrial imaging.…”
Section: Introductionmentioning
confidence: 99%